Prototype Design of Arduino-based Automatic Portable Anthropometric and Health Nutrition Assessment Tool - Ardianto, Efri Tri; Oktafa, Huda; Husin, H.; Afriansyah, Faisal Lutfi; Pratiwi, Berlina Yudha; Elisanti, Alinea Dwi (P3M Politeknik Negeri Jember, 2025)
The development of mobile-based applications has gained significant momentum, especially in developing countries like Indonesia. The Covid-19 pandemic has accelerated technological disruption, prompting a shift from manual to mobile-based systems. Advances in information technology have encouraged researchers to develop height measuring devices that are portable, efficient, fast and easy to use. It was new challenge in migrating from print and manual based systems to mobile based systems. The aim of this research is to design and develop a prototype for an arduino-based portable tool for anthropometric and nutritional assessment. The method used is the Prototype model method so it requires a systematic and sequential approach step by step. The tools used are ESP32 WROOM Microcontroller, ESP32 Expansion Breakout Board, HC-SR04 Ultrasonic Sensor, HX-711 Load cell Sensor, 20x4 I2C LCD. The developed anthropometric detection tool automatically determines nutritional status by measuring the weight and height of both children and adults. It is two separate tools that must be connected via WiFi Hotspot, the data from the two sensors will be processed via an Android application. In conclusion, this portable tool offers a user-friendly design compared to previously developed tools, enabling more effective and efficient nutritional status assessments.